A high-conductivity porous carbon carrier based on recycled graphite residue and a silicon-carbon negative electrode material and a preparation method thereof

CN123002835APending Publication Date: 2026-10-30YINGKOU SANZHE NEW MATERIALS IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611277264.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]然而,废石墨渣在电池循环使用后晶格缺陷增多,且传统的炉管活化方式处理时间长、能耗极高,在长时间高温处理过程中石墨层片容易过度剥落而转变为无序碳,从而丧失石墨本征的高导电性和高压实密度优势

Benefits of technology

第一,本发明采用微波辅助快速碱活化法处理回收的废石墨渣,微波活化时间由传统方法的3小时至5小时缩短至10分钟至15分钟,能耗降低80%以上。同时,原料为废旧电池回收的废石墨渣,无需使用昂贵的石油化工产品或新制石墨,极大降低了高导电多孔碳载体及化学气相沉积硅碳负极材料的生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002835A_ABST
    Figure CN123002835A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium battery negative electrode material preparation and solid waste recycling, and particularly relates to a high-conductivity porous carbon carrier based on recycled waste graphite residue and a silicon-carbon negative electrode material and a preparation method thereof. The recycled waste graphite residue is mixed with potassium hydroxide and potassium carbonate, and then microwave heating activation is performed, the temperature is raised to 800 DEG C to 850 DEG C within 3 minutes to 5 minutes and maintained for 10 minutes to 15 minutes, after water washing, acid washing and water washing to neutral, drying is performed, and a high-conductivity porous carbon carrier is obtained; then the carrier is placed in a chemical vapor deposition reactor, silane gas is introduced to deposit nano-silicon, and finally a carbon layer is coated to obtain a chemical vapor deposition silicon-carbon negative electrode material. The application realizes high-value recycling of the waste graphite residue, the microwave activation time is short, the energy consumption is low, the prepared carrier has high conductivity and rich pore structure, and the silicon-carbon negative electrode material has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery anode material preparation and solid waste recycling technology. Specifically, it relates to a highly conductive porous carbon support and silicon-carbon anode material based on recycled waste graphite slag and its preparation method. More specifically, it relates to a method for preparing a highly conductive porous carbon support by microwave rapid alkaline activation of recycled waste graphite slag from lithium batteries, and using the support for chemical vapor deposition of silane gas to construct a high-performance silicon-carbon anode material. Background Technology

[0002] Silicon-carbon composite materials are the core anode materials for next-generation high-energy-density lithium batteries. Currently, the raw materials for producing high-quality porous carbon supports mainly come from petrochemical products (such as asphalt and phenolic resin) or expensive newly produced graphite, resulting in high production costs for chemical vapor deposition silicon-carbon materials, which seriously hinders their commercial application in large-scale power batteries.

[0003] Meanwhile, with the continuous growth of lithium battery ownership, tens of thousands of tons of waste graphite slag from retired lithium battery anodes face the predicament of not being able to be efficiently recycled. If this waste graphite slag can be transformed into a conductive carrier for high-performance chemical vapor deposition silicon-carbon anodes, it will not only significantly reduce the raw material cost of silicon-carbon anodes but also achieve closed-loop green recycling of batteries.

[0004] However, waste graphite slag exhibits increased lattice defects after battery recycling, and traditional furnace tube activation methods are time-consuming and energy-intensive. During prolonged high-temperature processing, graphite layers are prone to excessive peeling, transforming into disordered carbon and thus losing the inherent high conductivity and high compaction density advantages of graphite. Therefore, there is an urgent need in this field for a process that can rapidly create pores without damaging the highly conductive lattice structure of the graphite core. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by proposing a microwave-assisted rapid alkali activation method. Using recycled waste graphite slag as raw material, it rapidly and with low energy consumption constructs a porous carbon carrier possessing both macropores and mesopores. Microwave heating is characterized by selectivity and volumetric heating. The trace metal impurities (copper, nickel, iron, etc.) remaining in the waste graphite slag and the carbon matrix itself are excellent microwave absorbers, rapidly heating to the reaction temperature within minutes. In the microwave field, the potassium hydroxide / potassium carbonate activator undergoes a rapid carbothermic reaction with the graphite surface, creating explosive pores on the surface and at defects of the graphite particles. Meanwhile, under microwave radiation, the highly ordered core regions inside the graphite do not have enough time to react with the alkali, thus perfectly preserving the highly conductive pathways and high-density framework of the graphite particles.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A method for preparing a highly conductive porous carbon support and silicon-carbon anode material based on recycled waste graphite slag includes the following steps: Step 1: Mix the recycled waste graphite slag with an activator to obtain a mixture, wherein the activator contains potassium hydroxide and potassium carbonate; Step 2: Place the mixture in a microwave reactor and activate it by microwave heating under a protective atmosphere, so that the mixture is heated to 800°C to 850°C within 3 to 5 minutes, and maintained at 800°C to 850°C for 10 to 15 minutes to obtain microwave activated material; Step 3: The microwave-activated material is sequentially washed with water, acid-washed, and washed with water until neutral, and then dried to obtain a highly conductive porous carbon support. Step 4: Place the highly conductive porous carbon support in a chemical vapor deposition reactor, introduce a mixture of silane gas and carrier gas, and perform chemical vapor deposition at 450°C to 500°C to deposit nano-silicon on the highly conductive porous carbon support to obtain a silicon-carbon composite material. Step 5: Coat the surface of the silicon-carbon composite material with a carbon layer to obtain a chemical vapor deposition silicon-carbon anode material.

[0007] In some embodiments of the present invention, the mass ratio of potassium hydroxide to potassium carbonate in the activator is 1:1; and the mass ratio of the recovered waste graphite slag to the activator is 1:0.6.

[0008] In some embodiments of the present invention, the microwave power in the microwave heating activation step is 1.5kW to 3.0kW.

[0009] In some embodiments of the present invention, before mixing the recycled waste graphite slag with the activator, the organic matter in the recycled waste graphite slag is first removed; after mixing the recycled waste graphite slag with the activator, water is added to moisten it and it is extruded into particles of 2 mm to 5 mm, and then pre-dried.

[0010] In some embodiments of the present invention, the pickling is performed by washing with hydrochloric acid at 60°C to 70°C for 2 to 4 hours.

[0011] In some embodiments of the present invention, the highly conductive porous carbon support has a specific surface area of ​​250 m² / g to 300 m² / g, a pore volume of 0.75 cm³ / g to 0.95 cm³ / g, and a powder conductivity of 80 S / cm to 110 S / cm.

[0012] In some embodiments of the present invention, the chemical vapor deposition is carried out in a fluidized bed chemical vapor deposition reactor; the carrier gas is argon; the volume percentage of the silane gas in the mixed gas is 5% to 10%; the chemical vapor deposition time is 2 to 3 hours; and the silicon-carbon composite material has a silicon mass percentage of 25% to 30%.

[0013] In some embodiments of the present invention, coating the surface of the silicon-carbon composite material with a carbon layer comprises: coating the surface of the silicon-carbon composite material with coal tar pitch, and then carbonizing it at 750°C to 850°C for 1.5 to 2.5 hours in an inert atmosphere; the mass of the carbon layer accounts for 4% to 6% of the total mass of the chemical vapor deposition silicon-carbon anode material.

[0014] The present invention also provides a chemical vapor deposition silicon-carbon anode material, which is prepared by the above preparation method.

[0015] In some embodiments of the present invention, the chemical vapor deposition silicon-carbon anode material comprises a highly conductive porous carbon support, nano-silicon deposited on the surface and in the pores of the highly conductive porous carbon support, and a carbon layer covering the outer surface of the nano-silicon.

[0016] Compared with the prior art, the present invention has the following beneficial effects: First, this invention employs a microwave-assisted rapid alkaline activation method to treat recycled waste graphite slag, reducing the microwave activation time from 3 to 5 hours in traditional methods to 10 to 15 minutes, and lowering energy consumption by more than 80%. Simultaneously, the raw material is waste graphite slag recycled from waste batteries, eliminating the need for expensive petrochemical products or newly produced graphite, significantly reducing the production costs of highly conductive porous carbon carriers and chemical vapor deposition silicon-carbon anode materials.

[0017] Secondly, this invention achieves a precise balance between surface pore formation and the high conductivity of the graphite core region through microwave confinement and rapid activation. Microwave energy directly acts on the microscopic electric dipoles of waste graphite particles, generating an extremely high local thermal effect. Potassium hydroxide and potassium carbonate undergo a rapid carbothermic reaction with the graphite surface in the microwave field. Pore formation only occurs at the periphery of the graphite and at microcracks, while the highly ordered core region inside the graphite is well preserved, ensuring the high crystallinity and high conductivity of the graphite core.

[0018] Third, the highly conductive porous carbon support obtained by this invention has abundant macropores and mesopores on its surface, with pore volumes ranging from 0.75 cm³ / g to 0.95 cm³ / g, which is beneficial for the efficient deposition and uniform distribution of silicon in chemical vapor deposition. These abundant mesopores and macropores on the surface can effectively buffer the volume stress generated during the lithium insertion / extraction process of nano-silicon, preventing silicon particles from falling off, thereby significantly improving the cycle stability of silicon-carbon anode materials.

[0019] Fourth, the chemical vapor deposition silicon-carbon anode material prepared by this invention can maintain a capacity retention of 88.2% and an initial coulombic efficiency of 87.0% after 800 cycles at a current density of 0.5C. It exhibits excellent electrochemical performance, comparable to that of silicon-carbon materials using newly prepared porous graphite, while also realizing the high-value recycling of waste graphite. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 This is a process flow diagram of the preparation method of highly conductive porous carbon support and silicon-carbon anode material based on recycled waste graphite slag according to the present invention. Detailed Implementation

[0021] The present invention will now be clearly and completely described in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are merely a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0022] In the description of this invention, the term "recycled waste graphite slag" refers to graphite slag recovered from retired lithium-ion battery anode sheets, which has undergone organic matter removal treatment before use. The term "highly conductive porous carbon support" refers to a porous carbon material with high conductivity and abundant pore structure obtained after microwave activation, washing, and purification. The term "chemical vapor deposition silicon-carbon anode material" refers to the final anode material obtained by chemical vapor deposition of nano-silicon and coating with a carbon layer on a highly conductive porous carbon support substrate.

[0023] like Figure 1 As shown, this invention provides a method for preparing a highly conductive porous carbon support and silicon-carbon anode material based on recycled waste graphite slag, comprising the following steps: Step 1: Mix the recycled waste graphite slag with an activator to obtain a mixture, wherein the activator contains potassium hydroxide and potassium carbonate; Step 2: Place the mixture in a microwave reactor and activate it by microwave heating under a protective atmosphere, so that the mixture is heated to 800°C to 850°C within 3 to 5 minutes, and maintained at 800°C to 850°C for 10 to 15 minutes to obtain microwave activated material; Step 3: The microwave-activated material is sequentially washed with water, acid-washed, and washed with water until neutral, and then dried to obtain a highly conductive porous carbon support. Step 4: Place the highly conductive porous carbon support in a chemical vapor deposition reactor, introduce a mixture of silane gas and carrier gas, and perform chemical vapor deposition at 450°C to 500°C to deposit nano-silicon on the highly conductive porous carbon support to obtain a silicon-carbon composite material. Step 5: Coat the surface of the silicon-carbon composite material with a carbon layer to obtain a chemical vapor deposition silicon-carbon anode material.

[0024] In the activator, the mass ratio of potassium hydroxide to potassium carbonate is 1:1; the mass ratio of the recovered waste graphite slag to the activator is 1:0.6.

[0025] In the microwave heating activation step, the microwave power is 1.5kW to 3.0kW.

[0026] It should be further explained that before mixing the recycled waste graphite slag with the activator, the organic matter in the recycled waste graphite slag is first removed; after mixing the recycled waste graphite slag with the activator, water is added to moisten it and it is extruded into particles of 2mm to 5mm, and then pre-dried.

[0027] The pickling process involves washing with hydrochloric acid at 60°C to 70°C for 2 to 4 hours.

[0028] The highly conductive porous carbon support has a specific surface area of ​​250 m² / g to 300 m² / g, a pore volume of 0.75 cm³ / g to 0.95 cm³ / g, and a powder conductivity of 80 S / cm to 110 S / cm.

[0029] The chemical vapor deposition is carried out in a fluidized bed chemical vapor deposition reactor; the carrier gas is argon; the volume percentage of the silane gas in the mixed gas is 5% to 10%; the chemical vapor deposition time is 2 to 3 hours; and the silicon-carbon composite material has a silicon mass percentage of 25% to 30%.

[0030] The carbon coating on the surface of the silicon-carbon composite material includes: coating the surface of the silicon-carbon composite material with coal tar pitch, and then carbonizing it at 750°C to 850°C for 1.5 to 2.5 hours in an inert atmosphere; the mass of the carbon layer accounts for 4% to 6% of the total mass of the chemical vapor deposition silicon-carbon anode material.

[0031] The present invention also provides a chemical vapor deposition silicon-carbon anode material, which is prepared by the aforementioned preparation method. The chemical vapor deposition silicon-carbon anode material comprises a highly conductive porous carbon support, nano-silicon deposited on the surface and pores of the highly conductive porous carbon support, and a carbon layer covering the outer surface of the nano-silicon.

[0032] The highly conductive porous carbon support is prepared by steps one to three, and the nano-silicon is deposited on the surface and pores of the highly conductive porous carbon support, with the carbon layer covering the outer surface of the nano-silicon.

[0033] The present invention will now be described in detail with reference to specific embodiments.

[0034] Example 1 Step 1: Take 50g of recycled waste graphite slag and remove the organic matter from it beforehand. Mix the recycled waste graphite slag after removing the organic matter with 15g of potassium hydroxide and 15g of potassium carbonate (i.e., the mass ratio of potassium hydroxide to potassium carbonate is 1:1, and the mass ratio of recycled waste graphite slag to activator is 1:0.6). Add 10mL of water to moisten and stir evenly. Then, extrude it into 2mm to 5mm particles and pre-dry it at 105℃ to obtain a mixture. Pre-drying removes moisture from the mixture, preventing rapid vaporization of moisture during subsequent microwave heating that could cause particle breakage. Pre-removing organic matter from the recycled waste graphite slag prevents the organic matter from carbonizing and producing disordered carbon during subsequent high-temperature microwave activation, thus ensuring the purity and structural order of the final porous carbon carrier. Extruding the mixture into 2mm to 5mm particles allows for uniform heat conduction within the particles during microwave heating and facilitates material transport during continuous industrial production.

[0035] Step 2: Place the dried mixture particles into a quartz crucible in a microwave reactor, and introduce high-purity nitrogen as a protective atmosphere. Set the microwave power to 2.0 kW and turn on microwave heating. The sample heats up to 820°C within 4 minutes, and is maintained at 820°C under microwave radiation for 12 minutes. Then, stop microwave heating and continue to introduce nitrogen to cool down, obtaining microwave-activated material.

[0036] During microwave heating activation, microwave energy directly acts on the microscopic electric dipoles of the recovered waste graphite particles, generating extremely high localized thermal effects. When potassium hydroxide and potassium carbonate are mixed in, the following rapid reaction occurs under microwave radiation: 6KOH+C→2K+3H2+2K2CO3; In the above reaction formula, K is potassium metal, H2 is hydrogen gas, K2CO3 is potassium carbonate, and C is carbon from graphite. The potassium metal produced in the reaction has extremely strong reducing and intercalation capabilities, and can react with carbon atoms at the edges of graphite sheets to create a pore-forming effect.

[0037] The above reaction can be completed within 10 to 15 minutes. Compared to the heating time of several hours to tens of hours in a traditional tube furnace, microwave activation can effectively control the reaction depth. Microwave heating has the characteristics of selective and volumetric heating. The trace metal impurities (copper, nickel, iron, etc.) and carbon matrix itself remaining in the recovered waste graphite slag are excellent microwave absorbers, which can rapidly heat up to the reaction temperature within minutes. In the microwave field, potassium hydroxide and potassium carbonate activators undergo a rapid carbothermic reaction with the graphite surface, creating explosive pores on the surface and at defects of the graphite particles. Under microwave radiation, the highly ordered core regions inside the graphite do not have enough time to react with the alkali, thus perfectly preserving the highly conductive pathways and high-density skeleton of the graphite particles. The entire activation process can be completed within 12 minutes, significantly reducing energy consumption compared to the heating time of several hours in a traditional tube furnace.

[0038] Step 3: Wash the microwave-activated material obtained in Step 2 three times with hot water and filter to recover potassium salt. Pour the washed solid into 500 mL of 2 mol / L hydrochloric acid and stir at 70°C for 3 hours to remove metal ion impurities (including copper, nickel, and iron ions). After filtration, wash with deionized water until neutral and dry to obtain a highly conductive porous carbon support, denoted as R-PSG-1. Hot water washing can recover the potassium salt byproduct generated during microwave activation, realizing further resource recycling; hot hydrochloric acid washing can remove activator residues and metal catalytic impurities entrained in the recovered waste graphite slag, avoiding these impurities from adversely affecting the subsequent chemical vapor deposition process and the electrochemical performance of the final silicon-carbon anode material; washing to neutral ensures no acid residue in the product, guaranteeing the purity of the highly conductive porous carbon support.

[0039] The performance of the highly conductive porous carbon support R-PSG-1 prepared in this embodiment was tested. Its specific surface area was 280 m² / g, pore volume was 0.78 cm³ / g, and powder conductivity was 98 S / cm. This highly conductive porous carbon support exhibits a rich pore structure, with numerous mesopores and macropores distributed on the surface. Furthermore, the overall morphology of the graphite particles remained intact, with no obvious lamellar peeling or structural collapse observed. This indicates that microwave rapid activation effectively created pores on the surface and preserved the graphite core structure.

[0040] Step 4: The highly conductive porous carbon support R-PSG-1 obtained in Step 3 is placed in a fluidized bed chemical vapor deposition reactor. A mixture of silane and argon gas with a volume percentage of 8% (i.e., silane gas volume percentage is 8%, argon gas is the carrier gas) is introduced, and chemical vapor deposition is performed at 480℃ for 2.5 hours. Nano-silicon is deposited on the highly conductive porous carbon support R-PSG-1 to obtain a silicon-carbon composite material, in which the silicon mass percentage is 27.5%. The fluidized bed chemical vapor deposition reactor allows the silane gas to fully contact the highly conductive porous carbon support, achieving uniform distribution of nano-silicon on the support surface and in the pores. The abundant macropores and mesopores on the surface of the highly conductive porous carbon support provide sufficient deposition space for nano-silicon, which is conducive to the diffusion of silane gas and the uniform nucleation and growth of nano-silicon. These abundant mesopores and macropores on the surface can buffer the volume stress generated by nano-silicon during the subsequent lithium insertion / extraction process, preventing silicon particles from falling off, thereby improving the cycle stability of the final silicon-carbon anode material.

[0041] Step 5: Coal tar pitch, accounting for 5% of the total mass of the chemical vapor deposition silicon-carbon anode material, is coated onto the surface of the silicon-carbon composite material obtained in Step 4. Then, the coating is carbonized at 800℃ for 2 hours in an inert atmosphere to obtain the chemical vapor deposition silicon-carbon anode material, denoted as Si@R-PSG-1@C. The carbon layer formed after carbonization coats the surface of the silicon-carbon composite material after nano-silicon deposition. This can suppress the volume expansion of nano-silicon during charge and discharge, while enhancing the overall conductivity and structural integrity of the material. As a protective layer, the carbon layer can isolate the electrolyte from direct contact with the nano-silicon, reducing side reactions and thus improving the material's initial coulombic efficiency and cycle stability.

[0042] The microstructure of the chemical vapor deposition silicon-carbon anode material Si@R-PSG-1@C prepared in this embodiment was observed. The nano-silicon particles were uniformly deposited on the surface and inside the pores of the highly conductive porous carbon support. The carbon layer completely covered the outer surface of the nano-silicon, forming a clear three-layer composite structure of "support-nano-silicon-carbon layer". This structure is conducive to giving full play to the synergistic effect of each component.

[0043] Electrochemical performance tests were conducted on the chemical vapor deposition silicon-carbon anode material Si@R-PSG-1@C prepared in this embodiment, using lithium metal as the counter electrode. At a current density of 0.1C, the initial reversible discharge capacity reached 1385 mAh / g, with an initial coulombic efficiency of 87.2%. After 1000 cycles at a current density of 1.0C, the specific capacity remained at 1180 mAh / g, with a capacity retention of 85.2%, demonstrating extremely high cycle stability.

[0044] Example 2 Step 1: Take 50g of recycled waste graphite slag and remove the organic matter from it beforehand. Mix the recycled waste graphite slag after removing the organic matter with 12g of potassium hydroxide and 12g of potassium carbonate (i.e., the mass ratio of potassium hydroxide to potassium carbonate is 1:1, and the mass ratio of recycled waste graphite slag to activator is 1:0.48). Add 10mL of water to moisten and stir evenly. Then, extrude it into particles of 2mm to 5mm and pre-dry it at 105℃ to obtain the mixture.

[0045] Step 2: Place the dried mixture particles into a quartz crucible in a microwave reactor, and introduce high-purity nitrogen as a protective atmosphere. Set the microwave power to 1.5kW and turn on microwave heating. The sample heats up to 800℃ within 5 minutes, and is maintained at 800℃ for 15 minutes under microwave radiation. Then, stop microwave heating and continue to introduce nitrogen to cool down, obtaining microwave-activated material.

[0046] The chemical reaction that occurs during microwave heating activation is the same as in Example 1, namely, potassium hydroxide reacts with carbon in graphite to produce metallic potassium, hydrogen gas and potassium carbonate.

[0047] Step 3: Wash the microwave-activated material obtained in Step 2 three times with hot water and filter to recover potassium salt. Pour the washed solid into 500 mL of 2 mol / L hydrochloric acid and stir at 60°C for 4 hours to remove metal ion impurities. After filtration, wash with deionized water until neutral and dry to obtain a highly conductive porous carbon support.

[0048] The high conductivity porous carbon support prepared in this embodiment was tested for performance. Its specific surface area was 250 m² / g, pore volume was 0.75 cm³ / g, and powder conductivity was 80 S / cm.

[0049] Step 4: Place the highly conductive porous carbon support obtained in Step 3 into a fluidized bed chemical vapor deposition reactor, introduce a mixture of silane gas and argon gas with a volume percentage of 5%, and perform chemical vapor deposition at 450°C for 3 hours to deposit nano-silicon on the highly conductive porous carbon support to obtain a silicon-carbon composite material with a silicon mass percentage of 25%.

[0050] Step 5: Coal tar pitch with a mass of 4% of the total mass of the silicon-carbon composite material obtained in Step 4 is coated on the surface of the composite material. Then, it is carbonized at 750°C for 2.5 hours in an inert atmosphere to obtain the silicon-carbon anode material, denoted as Si@R-PSG-2@C.

[0051] Electrochemical performance tests were conducted on the chemical vapor deposition silicon-carbon anode material Si@R-PSG-2@C prepared in this embodiment, using lithium metal as the counter electrode. At a current density of 0.1C, the initial reversible discharge capacity reached 1320 mAh / g, with an initial coulombic efficiency of 86.5%. After 1000 cycles at a current density of 1.0C, the specific capacity remained at 1100 mAh / g, with a capacity retention of 83.3%.

[0052] Example 3 Step 1: Take 50g of recycled waste graphite slag and remove the organic matter from it beforehand. Mix the recycled waste graphite slag after removing the organic matter with 18g of potassium hydroxide and 18g of potassium carbonate (i.e., the mass ratio of potassium hydroxide to potassium carbonate is 1:1, and the mass ratio of recycled waste graphite slag to activator is 1:0.72). Add 10mL of water to moisten and stir evenly. Then, extrude it into particles of 2mm to 5mm and pre-dry it at 105℃ to obtain the mixture.

[0053] Step 2: Place the dried mixture particles into a quartz crucible in a microwave reactor, and introduce high-purity nitrogen as a protective atmosphere. Set the microwave power to 3.0 kW and turn on microwave heating. The sample heats up to 850°C within 3 minutes, and is maintained at 850°C under microwave radiation for 10 minutes. Then, stop microwave heating and continue to introduce nitrogen to cool down, obtaining microwave-activated material.

[0054] The chemical reactions that occur during microwave heating activation are the same as in Example 1.

[0055] Step 3: Wash the microwave-activated material obtained in Step 2 three times with hot water and filter to recover potassium salt. Pour the washed solid into 500 mL of 2 mol / L hydrochloric acid and stir at 65°C for 2 hours to remove metal ion impurities. After filtration, wash with deionized water until neutral and dry to obtain a highly conductive porous carbon support.

[0056] The high conductivity porous carbon support prepared in this embodiment was tested for performance. Its specific surface area was 300 m² / g, pore volume was 0.95 cm³ / g, and powder conductivity was 110 S / cm.

[0057] Step 4: Place the highly conductive porous carbon support obtained in Step 3 into a fluidized bed chemical vapor deposition reactor, introduce a mixture of silane gas and argon gas with a volume percentage of 10%, and perform chemical vapor deposition at 500°C for 2 hours to deposit nano-silicon on the highly conductive porous carbon support to obtain a silicon-carbon composite material with a silicon mass percentage of 30%.

[0058] Step 5: Coal tar pitch with a mass of 6% of the total mass of the silicon-carbon composite material obtained in Step 4 is coated on the surface of the composite material. Then, the composite material is carbonized at 850°C for 1.5 hours in an inert atmosphere to obtain the silicon-carbon anode material, denoted as Si@R-PSG-3@C.

[0059] Electrochemical performance tests were conducted on the chemical vapor deposition silicon-carbon anode material Si@R-PSG-3@C prepared in this embodiment, using lithium metal as the counter electrode. At a current density of 0.1C, the initial reversible discharge capacity reached 1410 mAh / g, with an initial coulombic efficiency of 87.5%. After 1000 cycles at a current density of 1.0C, the specific capacity remained at 1210 mAh / g, with a capacity retention of 85.8%.

[0060] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the microwave heating activation in step two is replaced by traditional tube furnace heating activation. Specifically: Take the same mixture particles as in Example 1, place them in a tube furnace, and heat them to 820°C at a rate of 5°C / min under a nitrogen protective atmosphere. Activate them at 820°C for 3 hours, and then allow them to cool naturally to room temperature. The remaining steps are exactly the same as in Example 1.

[0061] The results showed that the porous carbon support prepared by conventional tube furnace activation had a powder conductivity of only 45 S / cm, far lower than the 98 S / cm of Example 1. This is because prolonged high-temperature treatment caused excessive exfoliation of graphite layers, transforming them into disordered carbon and losing the inherent high conductivity of graphite. The chemical vapor deposition silicon-carbon anode material prepared under the same conditions using this support had an initial reversible discharge capacity of only 1120 mAh / g at 0.1C, an initial coulombic efficiency of 82.1%, and a capacity retention of only 72.5% after 500 cycles at 1.0C, far lower than the performance level of Example 1.

[0062] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that only potassium hydroxide (30g) is used as an activator in step one, and potassium carbonate is not added. The other conditions are exactly the same as in Example 1.

[0063] The results showed that when potassium hydroxide was used as the activator alone, the reaction during microwave activation was too vigorous, making it difficult to control the pore depth. This resulted in partial etching of the highly ordered core region inside the graphite particles, and the conductivity of the resulting porous carbon support powder was only 62 S / cm. A chemical vapor deposition silicon-carbon anode material prepared under the same conditions using potassium hydroxide as the support exhibited an initial reversible discharge capacity of 1210 mAh / g at 0.1C, an initial coulombic efficiency of 84.3%, and a capacity retention of 78.5% after 800 cycles at 1.0C, all lower than the performance level of Example 1. This indicates that the combined use of potassium hydroxide and potassium carbonate is crucial for achieving a precise balance between surface pore formation and high conductivity in the core region.

[0064] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the carbon coating step in step five is omitted; that is, the silicon-carbon composite material is obtained directly after chemical vapor deposition of nano-silicon without pitch carbon coating. The remaining steps are exactly the same as in Example 1.

[0065] The results show that the uncoated silicon-carbon composite material has an initial reversible discharge capacity of 1420 mAh / g at 0.1C (slightly higher than Example 1), but its initial coulombic efficiency is only 75.3%, far lower than the 87.2% of Example 1. After 500 cycles at 1.0C, the capacity retention is only 68.5%, and the cycle stability is significantly lower than that of Example 1. This indicates that although the carbon coating slightly reduces the initial capacity, it can effectively improve the initial coulombic efficiency and long-term cycle stability, and is a key step in obtaining a chemical vapor deposition silicon-carbon anode material with excellent overall performance.

[0066] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a highly conductive porous carbon support and silicon-carbon anode material based on recycled waste graphite slag, characterized in that, Includes the following steps: Step 1: Mix the recycled waste graphite slag with an activator to obtain a mixture, wherein the activator contains potassium hydroxide and potassium carbonate; Step 2: Place the mixture in a microwave reactor and activate it by microwave heating under a protective atmosphere, so that the mixture is heated to 800°C to 850°C within 3 to 5 minutes, and maintained at 800°C to 850°C for 10 to 15 minutes to obtain microwave activated material; Step 3: The microwave-activated material is sequentially washed with water, acid-washed, and washed with water until neutral, and then dried to obtain a highly conductive porous carbon support. Step 4: Place the highly conductive porous carbon support in a chemical vapor deposition reactor, introduce a mixture of silane gas and carrier gas, and perform chemical vapor deposition at 450°C to 500°C to deposit nano-silicon on the highly conductive porous carbon support to obtain a silicon-carbon composite material. Step 5: Coat the surface of the silicon-carbon composite material with a carbon layer to obtain a chemical vapor deposition silicon-carbon anode material.

2. The preparation method according to claim 1, characterized in that, In the activator, the mass ratio of potassium hydroxide to potassium carbonate is 1:1; the mass ratio of the recovered waste graphite slag to the activator is 1:0.

6.

3. The preparation method according to claim 1, characterized in that, In the microwave heating activation step, the microwave power is 1.5kW to 3.0kW.

4. The preparation method according to claim 1, characterized in that, Before mixing the recycled waste graphite slag with the activator, the organic matter in the recycled waste graphite slag is removed; after mixing the recycled waste graphite slag with the activator, water is added to moisten it and it is extruded into particles of 2 mm to 5 mm, and then pre-dried.

5. The preparation method according to claim 1, characterized in that, The pickling process involves washing with hydrochloric acid at 60°C to 70°C for 2 to 4 hours.

6. The preparation method according to claim 1, characterized in that, The highly conductive porous carbon support has a specific surface area of ​​250 m² / g to 300 m² / g, a pore volume of 0.75 cm³ / g to 0.95 cm³ / g, and a powder conductivity of 80 S / cm to 110 S / cm.

7. The preparation method according to claim 1, characterized in that, The chemical vapor deposition is carried out in a fluidized bed chemical vapor deposition reactor; the carrier gas is argon; the volume percentage of the silane gas in the mixed gas is 5% to 10%; the chemical vapor deposition time is 2 to 3 hours; and the silicon-carbon composite material has a silicon mass percentage of 25% to 30%.

8. The preparation method according to claim 1, characterized in that, The carbon coating on the surface of the silicon-carbon composite material includes: coating the surface of the silicon-carbon composite material with coal tar pitch, and then carbonizing it at 750°C to 850°C for 1.5 to 2.5 hours in an inert atmosphere; the mass of the carbon layer accounts for 4% to 6% of the total mass of the chemical vapor deposition silicon-carbon anode material.

9. A chemical vapor deposition silicon-carbon anode material, characterized in that, The chemical vapor deposition silicon-carbon anode material, prepared by any one of claims 1 to 8, comprises a highly conductive porous carbon support, nano-silicon deposited on the surface and in the pores of the highly conductive porous carbon support, and a carbon layer covering the outer surface of the nano-silicon.

10. The chemical vapor deposition silicon-carbon anode material according to claim 9, characterized in that, The nano-silicon is deposited on the surface and in the pores of the highly conductive porous carbon support, and the carbon layer coats the outer surface of the nano-silicon.